2006
DOI: 10.1192/bjp.bp.104.007864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immigration detention and temporary protection on the mental health of refugees

Abstract: BackgroundOver the past decade, developed Western countries have supplied increasingly stringent measures to discourage those seeking asylum.AimsTo investigate the longer-term mental health effects of mandatory detention and subsequent temporary protection on refugees.MethodLists of names provided by community leaders were supplemented by snowball sampling to recruit 241 Arabic-speaking Mandaean refugees in Sydney (60% of the total adult Mandaean population). Interviews assessed posttraumatic stress disorder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
278
3
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(323 citation statements)
references
References 24 publications
25
278
3
10
Order By: Relevance
“…De nombreuses études scientifi ques et cliniques ont constaté que la détention des demandeurs d'asile était associée à un niveau élevé de symptômes psychiatriques (Keller et al, 2003 ;Ichikawa et al, 2006 ;Momartin et al, 2006 ;Steel et al, 2006 ;Silove et al, 2007 ;Robjant et al, 2009a ;Robjant et al, 2009 b). Au Royaume-Uni, après une déten-tion médiane de 30 jours, 76 % des demandeurs d'asile détenus étaient cliniquement déprimés, contre seulement 26 % des demandeurs d'asile non détenus, faisant partie du groupe témoin (Robjant et al, 2009b).…”
Section: L'impact De La Détention Sur La Santé Mentale Des Demandeursunclassified
See 1 more Smart Citation
“…De nombreuses études scientifi ques et cliniques ont constaté que la détention des demandeurs d'asile était associée à un niveau élevé de symptômes psychiatriques (Keller et al, 2003 ;Ichikawa et al, 2006 ;Momartin et al, 2006 ;Steel et al, 2006 ;Silove et al, 2007 ;Robjant et al, 2009a ;Robjant et al, 2009 b). Au Royaume-Uni, après une déten-tion médiane de 30 jours, 76 % des demandeurs d'asile détenus étaient cliniquement déprimés, contre seulement 26 % des demandeurs d'asile non détenus, faisant partie du groupe témoin (Robjant et al, 2009b).…”
Section: L'impact De La Détention Sur La Santé Mentale Des Demandeursunclassified
“…Ces deux instruments, bien validés, ont été utilisés dans de nombreuses études auprès de réfugiés et de demandeurs d'asile (Kleijin et al, 2001 ;Hollifi eld et al, 2002), incluant quatre autres études quantitatives sur la santé mentale des demandeurs d'asile détenus (Keller et al, 2003 ;Ichikawa et al, 2006 ;Momartin et al, 2006 ;Steel et al, 2006). Pour les besoins de notre étude, les instruments ont été traduits en français, espagnol, arabe, farsi, tamoul et ourdou, selon la procédure reconnue (Kleijin et al, 2001).…”
Section: L'impact De La Détention Sur La Santé Mentale Des Demandeursunclassified
“…31 A study comparing rates of anxiety, depression and PTSD among refugees and asylum-seekers from Iran and Iraq in Sydney found that those without refugee status were five times as likely to have PTSD as those with refugee status, though some of this discrepancy was explained by a difference in the groups' reported experience of traumatic events. 32 A recent Irish study found that 63% of asylum-seekers had PTSD symptoms, compared to 21% of refugees. 15 In this study, three-quarters of asylum-seekers endorsed symptoms of depression and anxiety, compared to one-third of refugees.…”
Section: Post Traumatic Stress Disordermentioning
confidence: 99%
“…Interviews with 14 adults and 20 children at a remote immigration detention center in Australia revealed that each person met criteria for at least one psychiatric disorder at the time of the interview (Steel et al, 2004). Furthermore, prolonged detention has been shown to have a long-term effect on the psychological health of refugees which persists after the detention (Steel et al, 2004(Steel et al, , 2006. Again at an Australian detention center, among the 16 adults and 20 children interviewed, all of the children had at least one parent with a psychiatric disorder (Mares & Jureidini, 2004).…”
Section: Psychosocial Effects Of Detention On Families: a Brief Overviewmentioning
confidence: 99%